Perspektif Generasi-Z terhadap Tahlilan Antara Budaya dan Syariat Islam - Jannah, Annisa I’zzatul; Khairunnisa, Alya Syafira; Vinaya, Aurell; M, Maya; Darpa, M. Mario; Afriyahnti, Nur Afipah; Suresman, Edi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study examines Generation Z’s perspective on tahlilan within cultural diversity and Islamic teachings. Growing up in the digital era, they have broad access to religious information, leading to varied views. Some see tahlilan as cultural heritage, while others question its accordance with Islamic law. Using a qualitative descriptive method with a phenomenological approach, data was gathered through interviews with Generation Z students at the University of Education Indonesia. The study explores their interpretation of tahlilan from both cultural and religious aspects. The findings reveal diverse opinions some view tahlilan as a non-obligatory tradition, while others see it as an act of worship due to its inclusion of prayer and dhikr. Additionally, tahlilan is regarded as a means to strengthen social bonds. This research highlights the evolving perception of religious traditions among younger generations. It provides insights for religious leaders to develop more relevant da’wah approaches and helps academics study the intersection of culture and Islam in the digital era.